Parental refusal to diphtheria vaccine: a fatal outcome - Amin Nordin, Syafinaz; Idris, Faridah; Awang Hama, Rukman; Ahmad Saad, Fathinul Fikri; Osman, Malina; Ghazali, Fadzillah; Isahak, Ilina (Malaysian Medical Association, 2013)
We present a case of a four-year-old boy who succumbed to diphtheria following incomplete course of immunisation, which included diphtheria vaccine. This case report focuses on the issues of parental refusal to vaccines and the development of "halal" vaccines for the prevention of infectious diseases.